(untitled) (World Economics and Finance Bulletin, 2024)
This study examined trade finance and the growth of Small and Medium Enterprises (SMEs) in Nigeria. The Pecking Order Theory which was proposed by Stewart Myers and Nicolas Majluf in 1984 anchored this current study. The study adopted a qualitative methodology and secondary data sources. The findings of the study showed that trade finance instruments enable SMEs to access working capital and manage cash flow more effectively which helps them to enter new markets, expand their operations, and increase their production capacity. Also, trade finance reduces barriers to international trade for SMEs by providing them with the capital required to participate in profitable cross-border transactions, by facilitating exports and imports, which are crucial for SMEs seeking to diversify their markets and increase their revenue streams. Lastly, the availability of trade finance improves SMEs’ relationships with suppliers by enabling them to secure better credit terms and negotiate favorable conditions for improving their performance. Based on the findings, this study concluded that trade finance plays a vital role in promoting and sustaining the growth of small and medium enterprises (SMEs) in Nigeria. It was recommended among others that policymakers and financial institutions should continue to support and develop trade finance mechanisms to empower SMEs, promote economic development, and strengthen Nigeria’s position in the global market